Standardized method for the determination of human erythrocyte membrane adenosine triphosphatases - Reinila, Matti; MacDonald, Ewen; Salem, Norman; Linnoila, Markku; Trams, Eberhard G. (Analytical biochemistry, 1982)
A standardized assay is described for the simultaneous determination of Mg 2+-ATPase, Na +, K +-ATPase, and Ca 2+-ATPase in human erythrocyte (RBC) membrane preparations. Membranes were prepared by lysis of RBCs in hypotonic buffer, and ATPase activity assays were based on the measurement of 32P-labeled inorganic phosphate release from [γ- 32P]ATP. The results obtained by this method were compared with those of colorimetric determination of inorganic phosphate and of ATP hydrolysis with high-performance liquid chromatography. The activity of the three enzymes was measured in RBC membranes obtained from 30 normal subjects. Repeated sampling of individuals over a 4-month period showed that interindividual differences were substantial, but that in each individual enzymatic activity was maintained in a narrow range by presumed homeostatic mechanisms. Statistical analysis of the data showed no interdependence of the three enzymes; a correlation of activity with age, sex, or phase of the menstrual cycle was not apparent. The values obtained for the Ca 2+-ATPase did not follow a normal distribution, and it is suggested that this enzyme has two phenotypic variants. The described method is sufficiently precise and economical to be recommended for adoption as standard procedure in clinical research.